Literature Study: Analysis of the Relationship Between Age and the Incidence of Postpartum Hemorrhage in Maternity Mothers - Winanda Putri Pratiwi, Tatut Isna; Afsari, Indah Ayu; Lailiyah, Syifa'ul (citeus, 2023)
Postpartum hemorrhage is the leading cause of maternal death worldwide with an incidence of 5 – 10 percent of all deliveries. Data shows a downward trend in maternal mortality in Indonesia in 1991 from 390 to 230 in 2020 per 100,000 live births. Maternal mortality is an important concern because being one of the indicators of health status and the success of health development, the reduction in maternal mortality rate is also a target in the Sustainable Development Goals (SDGs). In the SDGs, the target of reducing the maternal mortality rate is 70 per 100,000 live births by 2030. The preliminary study found cases of postpartum hemorrhage with risk age less than 20 years as many as 90 people (6.2 percent), bleeding with age more than 35 years as many as 40 people (2.7 percent). The purpose of this study was to conduct a literature study on the relationship between maternal age and postpartum hemorrhage. This study used 13 national journals obtained through Google scholar and Garuda (Digital Referral Guard). Based on the results of the study, 10 journals stated that there was a significant relationship between maternal age and postpartum hemorrhage, while 3 other journals showed that there was no significant relationship between maternal age and postpartum hemorrhage.